PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KARYAWAN MELALUI KEPUASAN KERJA KARYAWAN PRODUKSI BAGIAN JAMU TRADISIONAL UNIT KALIGAWE PT. NJONJA MENEER SEMARANG - Bayu Fadillah; Handoyo Djoko Widodo; Agung Budiatmo (Universitas Diponegoro, 2013)
Human resources is one factor that plays an important role in the effort to realize the goal of a company. Meanwhile, to achieve its goal, the company is highly dependent on the productivity of its employees. Seeing the importance of the role of human resources in realizing the objectives of the company, it would require a serious effort in the management of human resources in a company is to increase the productivity of human resources. One way to increase motivation by trying to satisfy all the needs of employees and create conditions conducive working environment, so that it can support the employee to be able to work well. In addition, job satisfaction also needs to be created in order to keep a good employee productivity. This study aimed to determine the effect of variable positive motivation, work environment and job satisfaction on employee productivity PT. Njonja Meneer. The population of this study are employees of the production unit Kaligawe Traditional Herbal PT. Njonja Meneer which amounts to 311 employees with Slovin formula samples used was 76 people by spreading using nonprobability sampling method (Systematic Random Sampling). Measurement scale using Likert scale. In the analysis of the data using simple linear regression, multiple regression and path analysis with SPSS 16.0. Based on these analysis of the data it is known Motivational variables affect Job Satisfaction of 42.5 percent. Work Environment Variables affect Job Satisfaction by 58.7 percent. Motivational variables affect employee productivity by 60.3 percent. Work Environment Variables affect employee productivity by 59.1 percent. Job Satisfaction variables affect employee productivity by 51.4 percent. Taken together Motivation and Work Environment on Job Satisfaction by 59.4 percent. Taken together Motivation, Work Environment and Job Satisfaction on Employee Productivity by 69.9 percent. This means better Motivation, Work Environment, Job Satisfaction and Employee Productivity is expected that the better. These results the management of PT. Njonja Meneer need to provide clear guidance related to the understanding of the task to be given to the employee in detail so that employees can get the job done properly. Besides, it is necessary to consider the condition of the work environment that provided the company with a way to optimize the function of the air vents for air circulation smoothly and provide adequate lighting as needed in each work unit. Companies also need to increase job satisfaction given to employees. This business can be done by providing the opportunity for promotions for employees who have good productivity and improve surveillance systems to better prioritize social approach.